2015
DOI: 10.5414/cn108473
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of calcitriol in treating glucocorticoidinduced osteoporosis in patients with nephrotic syndrome: an open-label, randomized controlled study

Abstract: Calcitriol may be more effective than calcium carbonate in preventing and treating GC-induced osteoporosis in patients with NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Die SLR erfolgte in Anlehnung an die 2017 aktualisierte Leitlinie des American College of Rheumatology (ACR) [19,20] 1 Bezüglich der Effekte einer Kalziumbzw. Vitamin-D-Monotherapie und der Kombination von Kalzium und Vitamin D3 ergab eine dreiarmige "openlabel" randomisiert kontrollierte Studie mit 66 GC-behandelten Patienten, dass die Behandlung mit Vitamin D (als Monotherapie) und Vitamin D plus Kalzium (0,81 g/cm 2 und 0,82 g/cm 2 ) mit signifikant höheren Knochenmineraldichtewerten an der LWS im Vergleich zur Kalziummonotherapie nach 24 Wochen assoziiert war (0,62 g/cm 2 , p < 0,05 jeweils) [23]. Auch in dieser Studie war die BMD in allen 3 Armen rückläufig.…”
Section: Systematische Literaturrechercheunclassified
“…Die SLR erfolgte in Anlehnung an die 2017 aktualisierte Leitlinie des American College of Rheumatology (ACR) [19,20] 1 Bezüglich der Effekte einer Kalziumbzw. Vitamin-D-Monotherapie und der Kombination von Kalzium und Vitamin D3 ergab eine dreiarmige "openlabel" randomisiert kontrollierte Studie mit 66 GC-behandelten Patienten, dass die Behandlung mit Vitamin D (als Monotherapie) und Vitamin D plus Kalzium (0,81 g/cm 2 und 0,82 g/cm 2 ) mit signifikant höheren Knochenmineraldichtewerten an der LWS im Vergleich zur Kalziummonotherapie nach 24 Wochen assoziiert war (0,62 g/cm 2 , p < 0,05 jeweils) [23]. Auch in dieser Studie war die BMD in allen 3 Armen rückläufig.…”
Section: Systematische Literaturrechercheunclassified
“…In addition, calcitriol directly affects the skeletal, intestinal, renal, and parathyroid systems. It enhances the sensitivity of the parathyroid glands to calcium and inhibits transcriptional activity of PTH gene and proliferation efficiency of parathyroid cells, thereby reducing secretion and synthesis of PTH [18,19]. However, it is essential to closely monitor patients' blood Ca and Pi concentrations when using calcitriol.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization and detoxification for vitamin D3 derivatives is 2-4 weeks and 7 to 30 days, and 4 to 7 days and 2 to 10 days for calcitriol. 18 For restoring the vitamin D resources in the body, the time required is 2-3-fold higher for vitamin D3 preparations compared to vitamin D2 derivatives. 15 Interventional strategies are required to prevent bone diseases in patients with nephrotic syndrome, and the efficacies of different preparations have been compared in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…15 Interventional strategies are required to prevent bone diseases in patients with nephrotic syndrome, and the efficacies of different preparations have been compared in some studies. Chen et al 18 reported the preferred form of vitamin D as calcitriol alone in comparison to calcium carbonate alone or their combination. They found no adverse effects in their study.…”
Section: Discussionmentioning
confidence: 99%